LONG-DISTANCE-RELAYED WATER VAPOR TRANSPORT EAST OF TIBETAN PLATEAU AND ITS IMPACTS - 周长艳 齐冬梅 李跃清 陈丹 (Journal of Tropical Meteorology, 2015)
This paper attempts to reveal a long-distance-relayed water vapor transport（LRWVT） east of Tibetan Plateau and its impacts. The results show that from August to October, east of Tibetan Plateau, there exists a unique LRWVT,and the water vapor from the South China Sea and the western Pacific can affect the Sichuan Basin, Northwest China and other Chinese regions far from the tropical sea through this way. From August to October, the precipitation of the region east of the Plateau is closely linked both in the intra-annual and inter-annual variations, and the LRWVT from the South China Sea and the western Pacific is an important connection mechanism. The large-scale circulation background of the LRWVT impacting the precipitation of the region east of the Plateau is as follows： At high levels,the South Asian High is generally stronger than normal and significantly enhances with its northward advance and eastward extension over the region east of the Plateau. At mid-level, a broad low pressure trough is over Lake Balkhash and its surroundings, and the Western Pacific Subtropical High（WPSH） is northward and westward located, and the western part of Sichuan Basin and the eastern part of Northwest China are located in the west and northwest edge of WPSH.